Wireless connectivity predicaments in gsm-based amr system: An empirical research - Suliman S.H.; Hashim W.; Ismail A.F.; Yahya A.S.; Khairolanuar M.H.; Sauti M.S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The convergence of Global System for Mobile Communication (GSM) and Information Communication Technology (ICT) allows the mobile and wireless application to be implemented in Automatic Meter Reading (AMR) system. In addition to the advancement of cellular technology and spectrum refarming, GSM-based AMR system is continuously facing propagation challenges that affect the stability of wireless connectivity. A field study was conducted to investigate the real reasons for having predicaments in coverage behaviour introduced by GSM-based AMR system for three local Internet Service Providers (ISPs) in Malaysia. The main objective of this study is to verify signal coverage performance at identified AMR locations that were reported having signal lost. We have categorized the challenges and depicted the signal quality readings that show signal performances for different service providers. The outcomes form the basis for our future development of cognitive network selection prototype for utility (gas, electricity, water) companies wireless communication smart grid. BEIESP.